Effect of hysteresis, infiltration and tensile stress on the strength of an unsaturated soil - Han, Khee Kwong. (2009)
Rain-induced landslides normally involve water infiltration into unsaturated soils. Unsaturated soils have high cohesion which implies the presence of tensile stress in the soils. Hysteresis (i.e., wetting and drying) is a common feature of unsaturated soils and it is expected to have some influence over the strength of the soils. Therefore, this thesis investigates the effect of tensile stress, hysteresis and stress path on the strength of an unsaturated soil.